Dissimilation, Assimilation and Vowel Reduction: Constraint Interaction in East Slavic Dialects with so-called Dissimilative Akan’e and Jakan’e - Nesset, Tore (Poljarnyj vestnik, 2002)
This paper presents an Optimality Theory-based analysis of  the unstressed vocalism in Russian. It is argued that an account of the so-called dissimilative akan’e and jakan’e patterns in terms of dissimilation alone is simplistic and that the vowel patterns in question arise as a result of complex interaction of three factors, viz. dissimilation, assimilation and vowel reduction.
Keywords: Russian; language; dialectology; vowel reduction; dissimilative akan’e; dissimilative